IAgent an intelligent agent for algorithm search in the internet - Jalandoni, Ma Victoria L. (1998)
Today, we witness the continuing growth of the Internet and this growth brings with it the need to cope up in terms of creating new technologies which would utilize the Internet to its full potential. One such technology, which is enjoying a great deal of research even as we speak, is the development of software applications which would effectively initiate and execute actions in behalf on the user. This thesis is an exploration into the emerging autonomous agent technology which will culminate with a working intelligent agent designed to index, search for and download documents from the internet pertaining to algorithms with the objective of providing students of Computer Science an alternative resource.